Metamaterial-based perfect absorbers for efficiently enhancing near field radiative heat transfer. (December 2015) - Zhou, Nan; Xu, Xianfan
Abstract: The fascinating capability of manipulating light using metamaterials (MMs) has inspired a significant amount of studies of using MMs for energy related applications. In this work we investigate MM-based perfect absorbers for enhancing near field radiative heat transfer, which is described by the fluctuation dissipation theorem. MM structures designed at two wavelengths are analyzed, corresponding to two working temperatures. Both electric and magnetic surface polaritons are found to contribute to heat transfer, while natural materials support only electric polaritons. The near-perfect absorption is demonstrated to be related to the modification of effective optical properties, which is important for enhancing radiative heat transfer efficiently. By comparing different designs, the bandwidth of the heat flux spectrum is found to increase with the absorption bandwidth, which is originated from the spatial field distributions. This study will contribute to the understanding of surface polaritons in near field radiative heat transfer and facilitate the optimization of MMs for near field heat transfer applications.